External voluntary care and school teaching (Práxis Educativa, 2023)
This is a theoretic-bibliographical study on the attentional development process, more specifically on external voluntary attention, according to the Cultural-Historical Psychology and its critique of the medicalization of education. The objective is to explain the psychic characteristics of voluntary external attention and possible implications for the school education of children in the early grades of Elementary School. Psychic functions have a history of formation, with social relationships as a necessary component, through internalizations of signs that form self-controlled internal capacities. External voluntary attention is marked by the transit of external signs to the intrapsychic condition of an internal voluntary attention in formation. As a result, it is concluded that children at this stage depend on the teacher’s guidance to be able to actively and voluntarily carry out study actions/activities, until the teaching objectives are reached, proving to be a relevant aspect of pedagogical planning in the early grades of Elementary School.Keywords: Psychic development. Voluntary attention. Schooling.